ASSESSMENT OF COMPETITIVENESS ON THE LIGHT INDUSTRY GOODS MARKET - Ismoilov Ravshanjon Baxriddinovich; Xurramov Zufar Inat o’g’li; Badiyev Baxtinur Bahodir o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article examines the status and development of the apparel market in Uzbekistan, and changes in its structure based on marketing research and evaluates the impact of changes in the retail segment of the apparel market, the composition of the consumer market of garments, and the changes in consumer segment. Based on the competitive position on the assortment of retail clothing, strategies for pushing the garments from China, Turkey and other countries into the domestic market for each assortment of clothing are identified. Changes in consumption by squeezing an assortment of competing countries from the domestic market are studied on the basis of panel research, and a matrix of factors influencing its formation and wardrobe formation.